PENANGGULANGAN KRISIS KESEHATAN AKIBAT BENCANA BANJIR DI KOTA SEMARANG TAHUN 2011 - Dismo Katiandagho (Jurnal Kesehatan Lingkungan, 2012)
Flooding is the inundation event (overflow) of water in certain areas as a result of water overflowing river / lake/ sea causing losses both material and non-material to humans and the environment. Disaster surveillance purposes and Matra are: 1) To determine the causes and impacts of flooding, 2) To know the health problems arising from floods, 3) To know the efforts made prior to the flood of catastrophic flooding, 4) To know the efforts made at the time of occurrence of floods, 5) To know the current dilakukanpada efforts after the floods. Methods of Disaster and surveillance activities are conducted descriptive Matra where the author wants to describe how penanggunalan health crisis due to floods in the city of Semarang. Population in Disaster surveillance and Matra were all officers involved in the response to the health crisis Semarang City Health Office and the Provincial Health Office of Central Java. Results of the implementation of surveillance activities and Matra Disaster is the time of flood and post-flood health problems usually arise in various residential areas and public areas are exposed to inundation. Health problems that arise include the following diseases: a) Acute Respiratory Infections (ARI), b) Diarrhea, c) Skin Diseases, d) Gastritis, e) accidents (injuries, electrocution, drowning, etc.), f) leptospirosis, g) Conjunctivitis, h) venomous animal bites (eg snakes, scorpions), i) abdominal typus, etc.. Cases of the disease is often significantly improved, some of which may even be of extraordinary events (KLB) which is not uncommon with death.